Organization of group activity of younger students in Ukrainian language lessons - Kovshar, O.V. (Pedagogy of Higher and Secondary Education, 2022)
In the article an author considers notion group work. Accents attention on the types of groups and psychology - pedagogical terms of their unton at junior schoolbayr, determines the tasks on the lessons of Ukrainian for implementation in groups.